1980
DOI: 10.1038/286533a0
|View full text |Cite
|
Sign up to set email alerts
|

Presence of integrated hepatitis B virus DNA sequences in cellular DNA of human hepatocellular carcinoma

Abstract: Hepatitis B virus (HBV) may be one of the agents involved in the aetiology of human primary liver cancer. This hypothesis is supported by (1) the similarity between the geographical distribution of chronic carriers of the viral surface antigen (HBsAg) and that of hepatocellular carcinoma (HCC); (2) the increase in the prevalence of HBV markers in serum of patients with primary liver cancer when compared with the general population; (3) the observation that HBV infection precedes the development of the tumour. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
272
0
5

Year Published

1982
1982
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 578 publications
(286 citation statements)
references
References 9 publications
9
272
0
5
Order By: Relevance
“…It has been suggested that a low level of DHBV replication might occur in some such livers, although it was at the limit of sensitivity of a dot blot assay. We have taken advantage of the high specificity and sensitivity of SB-PCR, which has been found 104 times more sensitive than the dot-blot assay (Brechot et al, 1980;Ogston et al, 1982;Marion et al, 1986). The previous reports on Chinese duck HCC revealed only a single case of DHBV DNA integration (Yokosuka et al, 1985) and in this study we report a second case.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…It has been suggested that a low level of DHBV replication might occur in some such livers, although it was at the limit of sensitivity of a dot blot assay. We have taken advantage of the high specificity and sensitivity of SB-PCR, which has been found 104 times more sensitive than the dot-blot assay (Brechot et al, 1980;Ogston et al, 1982;Marion et al, 1986). The previous reports on Chinese duck HCC revealed only a single case of DHBV DNA integration (Yokosuka et al, 1985) and in this study we report a second case.…”
Section: Discussionmentioning
confidence: 69%
“…In fact HCC has been found only in domestic brown ducks from a single area of China, Qidong and only four Chinese duck HCCs had so far been described (Omata et al, 1983;Marion et al, 1984;Yokosuka et al, 1985). Unlike the HCCs in human and woodchuck in which integrated HBV and WHV DNA in the host genome has regularly been observed (Brechot et al, 1980, Ogston et al, 1982, only a single case of Chinese duck HCC with integrated DHBV DNA has to date been reported (Yokosuka et al, 1985). Qidong is an area of high human HCC incidence in China, in which both HBV and aflatoxin B1 (AFB1) are risk factors (Sun et al, 1986).…”
mentioning
confidence: 99%
“…Unlike retroviruses, which integrate viral DNA into the host genome, hepadnavirus genomes are not integrated routinely but, instead, are maintained in the nucleus of infected cells in vivo as a pool of episomal covalently closed circular (CCC) DNA molecules. 9 Although the integration of HBV DNA in human liver has been reported, 10 it is not an obligatory part of the HBV lifecycle. HBV does not encode any machinery for integration into the host genome, and integration is not required for HBV replication.…”
mentioning
confidence: 99%
“…The reverse transcription of the RNA pregenome and second-strand HBV DNA synthesis results in low-molecular-weight replicative intermediates, whereas the HBV DNA that integrates into the host' s genome can be detected as high-molecular-weight species on Southern blot. 18,19 Similar to retroviral integration at the site of the long terminal repeats, HBV DNA generally inserts into DNA flanked by the direct repeat regions, which share sequence homology with the U5 region of murine leukemia virus long terminal repeats. [20][21][22] The genomic organization of the HBV direct repeat region provides a potential strategy for the detection of replicating virus when only minute quantities of HBV DNA are present (Fig.…”
mentioning
confidence: 99%